Sistem Informasi Manajemen Arsip Elektronik (E-Arsip) Berbasis Microsoft Access Terhadap Efektivitas Penemuan Kembali Arsip Pada SMKN 4 Surabaya - Alvina Tri Amalia; Lifa Farida Panduwinata (Universitas Negeri Surabaya, 2022)
Records management plays important roles in an agency or organization. Technology develops rapidly along with time. In terms of electronic-based management information systems, the researcher tries to innovate to improve the conventional archive management system using a Microsoft Access-based archive application system. This study aims to (1) determine the process of designing an Electronic Archive Management Information System (E-Archive) using Microsoft Access and (2) determine the effectiveness of the E-archive design using Microsoft Access for the Administration of SMKN 4 Surabaya. This Research & Development (R&D) used the ADDIE development model. The test subjects were 3 Administrative Archives of SMKN 4 Surabaya. Quantitative and qualitative data were obtained from validation sheets and questionnaires. The validators involved were Design Experts, Media Experts, and Practitioners. Data were analyzed using Accuracy Figures adapted from Liang Gie. Based on the results of the study, it can be concluded that (1) Microsoft Access-based archive applications get an average percentage of 92.8% with